Critical Thinking Skills Integrated in English Language Materials in Vocational School - Hanip Pujiati; Alvin Harya Putra; Aprillia Anggraani (Future Science, 2024)
This paper presents the results of a study aiming to investigate the critical thinking skill integration in English learning materials involving three Vocational State Schools in Jakarta, Indonesia. The study used the content analysis method by Klaus Krippendorff's to examine textual, visual, or multimedia materials. It involves categorizing, coding, and analyzing content to uncover critical thinking indicators. The steps are to choose a representative sample of the learning materials to be analyzed, create the indicators of each element of critical thinking skills, and analyze the selected content by systematically categorizing and coding data based on the established criteria to identify critical thinking indicators, The data analysis procedures were data reduction, data presentation, and conclusion or drawing a verification after analyzing all the data which have completed aspects of English learning materials. The results show that all critical thinking skills elements are integrated into English learning materials and the most frequent indicator is the “interpretation”. The Critical thinking indicators in learning materials are interpretation denotes the highest grade, succeeded by Explanation, Self-regulation, Analysis, Inference, and Evaluation. It is recommended that teachers are advised to design adaptable English learning materials suited to specific majors and prompt the students to think critically through English learning materials.